The urban sketching handbook : 101 sketching tips - Bower, Stephanie ([The Urban Sketching Handbook series], 2020)
"Illustrator, architect, and international workshop instructor and Urban Sketcher Stephanie Bower has collected 101 of her best insider drawing tips, hacks, and techniques and shares them in this fully illustrated, portable book. Learn shortcuts to getting your perspective right, determining your composition, and balancing your light and shadow"--